2016
DOI: 10.1111/gbb.12301
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive flexibility deficits in a mouse model for the absence of full‐length dystrophin

Abstract: Duchenne muscular dystrophy (DMD) is a progressive muscle-wasting disorder, caused by mutations in the DMD gene and the resulting lack of dystrophin. The DMD gene has seven promoters, giving rise to multiple full-length and shorter isoforms. Besides the expression of dystrophin in muscles, the majority of dystrophin isoforms is expressed in brain and dystrophinopathy can lead to cognitive deficits, including intellectual impairments and deficits in executive function. In contrast to the muscle pathology, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 62 publications
(135 reference statements)
2
39
2
Order By: Relevance
“…Indeed, in 2009 a group showed that this model did not display an anxiety-like phenotype in the elevated plus maze [24]. However, other recent studies indicate a deficit in the light-dark choice anxiety test [25,42]. Moreover, another group demonstrated anxiety-like and depression-like behaviors in mdx mice, associated with decreased BDNF (Brain derived neurotrophic factor) levels [43].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in 2009 a group showed that this model did not display an anxiety-like phenotype in the elevated plus maze [24]. However, other recent studies indicate a deficit in the light-dark choice anxiety test [25,42]. Moreover, another group demonstrated anxiety-like and depression-like behaviors in mdx mice, associated with decreased BDNF (Brain derived neurotrophic factor) levels [43].…”
Section: Discussionmentioning
confidence: 99%
“…The light↔dark transitions test was conducted as previously described to assess anxiety-like conflict behavior in mice. 21,22 Initially, mice were placed into the brightly lit compartment (~400 lux; 20×15×25 cm; facing away from the opening) and allowed to explore freely between the light and dark chambers (20×15×25 cm) for 10 min. The time spent in the light side chamber and the total transitions between the two sides of the chamber were automatically recorded using Noldus Observer software (Ethovision 11.0) and considered indices of anxiety and overall activity, respectively.…”
Section: Light↔dark Transitionsmentioning
confidence: 99%
“…Similar to patients, absence of Dp427 in the mdx mouse is associated with behavioral and social impairments, such as enhanced freezing response in reaction to danger and altered ultrasonic vocal communication [ 31 33 ]. Learning and memory performance were also found to be impaired in some studies [ 34 37 ], though others report that spatial memory is largely unaffected [ 38 , 39 ]. Brain morphology of mdx mice has been reported in two studies [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%